2011
DOI: 10.1308/147870811x13137608454803
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of staged bilateral knee replacements

Abstract: INTRODUCTION The aim of this study was to compare the functional outcome between the first and second knee replacement in patients undergoing staged bilateral total knee arthroplasty. METHODS We identified 64 patients who had bilateral knee replacements and had at least one year of postoperative outcome studies. Data on pain scores, walking ability, use of walking aids, range of movement, instability, muscle strength, WOMAC ® (Western Ontario and McMaster Universities) scores, SF-12 (Short Form 12) scores, Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 14 publications
4
12
0
Order By: Relevance
“…Like us, Gabr et al [19] found similar KSS, WOMAC and SF12-physical scores between knees at the last follow-up, and better SF12-mental score for the second knee compared to the first. Other studies reported no significant differences between both knees at the last followup [9,11].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Like us, Gabr et al [19] found similar KSS, WOMAC and SF12-physical scores between knees at the last follow-up, and better SF12-mental score for the second knee compared to the first. Other studies reported no significant differences between both knees at the last followup [9,11].…”
Section: Discussionsupporting
confidence: 65%
“…Some authors [5,19] have reported higher patient expectation for the second than for the first TKA. Gabr et al [20] found improved function and psychological well-being after the second surgery.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“… 10 , 11 Several studies have reported mixed results when comparing the first and second knee arthroplasties. Gabr et al 4 showed a shorter length of stay along with improved walking aid requirement and psychological well-being (SF-12) in the second knee. Kim et al 5 reported greater VAS pain and analgesic requirement in the second knee, whereas Sun et al 6 showed that VAS pain was initially greater in the second knee, but that no difference existed in pain at 72 hours after surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Outcomes after staged knee arthroplasty have been extensively studied, and differences have been shown between the first and second operated knees. 4 5 6 There have been a number of previous studies that evaluated overall outcomes in BSA, 7 8 9 but little is known regarding differences between the first and second operated shoulders. The purpose of this study was to compare the efficacy and overall improvement in function, pain, general health, motion, and satisfaction between the first and second operated shoulders in patients with BSA.…”
mentioning
confidence: 99%
“…A few studies also investigated differences in pain and physical function following simultaneous bilateral or staged bilateral TKR. While one study indicates functional improvements following simultaneous bilateral TKR [14], another study reports positive outcome with respect to pain and physical function following staged bilateral TKR [15]. However, lack of control groups in these studies reduce the external validity of the results.…”
Section: Introductionmentioning
confidence: 99%